Bangladesh : studies on the social dimension of globalization - Paratian, Rajendra (ILO GenevaCH, 2001)
Addresses the issue of whether trade liberalization undertaken in the 1990s may have contributed to paving the way for Bangladesh's economic take-off. Examines measures that could help improve the benefits from reforms while reducing social costs.